2022
DOI: 10.3390/biomedicines10102428
|View full text |Cite
|
Sign up to set email alerts
|

EEG Markers of Treatment Resistance in Idiopathic Generalized Epilepsy: From Standard EEG Findings to Advanced Signal Analysis

Abstract: Idiopathic generalized epilepsy (IGE) represents a common form of epilepsy in both adult and pediatric epilepsy units. Although IGE has been long considered a relatively benign epilepsy syndrome, a remarkable proportion of patients could be refractory to treatment. While some clinical prognostic factors have been largely validated among IGE patients, the impact of routine electroencephalography (EEG) findings in predicting drug resistance is still controversial and a growing number of authors highlighted the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…46 For example, several studies have investigated the relationship between EEG abnormalities and outcomes, often providing conflicting or incongruous evidence; whilst it is probable that some association exists, it is likely that EEG patterns and features influence/are mediated by external factors, and further multivariable research is required to determine how. 47 To facilitate application and future evaluation (as in with systematic reviews) it is recommended that prediction models be designed and reported in a systematic manner, such as is outlined by Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) guidelines. 48 Adherence to a predefined set of guidelines, such as TRIPOD, helps to ensure that the risk of bias (RoB; systematic error) and applicability concerns (AC) in the resultant study are kept to a minimum.…”
Section: Second-line Therapiesmentioning
confidence: 99%
“…46 For example, several studies have investigated the relationship between EEG abnormalities and outcomes, often providing conflicting or incongruous evidence; whilst it is probable that some association exists, it is likely that EEG patterns and features influence/are mediated by external factors, and further multivariable research is required to determine how. 47 To facilitate application and future evaluation (as in with systematic reviews) it is recommended that prediction models be designed and reported in a systematic manner, such as is outlined by Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) guidelines. 48 Adherence to a predefined set of guidelines, such as TRIPOD, helps to ensure that the risk of bias (RoB; systematic error) and applicability concerns (AC) in the resultant study are kept to a minimum.…”
Section: Second-line Therapiesmentioning
confidence: 99%
“…33 For example, several studies have investigated the relationship between EEG abnormalities and outcomes, often providing conflicting or incongruous evidence; although it is probable that some association exists, it is likely that EEG patterns and features influence/are mediated by external factors, and further multivariable research is required to determine how. 34 To facilitate application and future evaluation (as in with systematic reviews) it is recommended that prediction models be designed and reported in a systematic manner, such as is outlined by Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis (TRIPOD) guidelines. 35 Adherence to a predefined set of guidelines, such as TRIPOD, helps to ensure that the risk of bias (RoB; systematic error) and amount of applicability concerns in the resultant study are kept to a minimum.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Single biomarkers (quantifiable properties indicative of normal biological processes) in epilepsy are thought to lack the granularity and robustness necessary to allow for clinical application 33 . For example, several studies have investigated the relationship between EEG abnormalities and outcomes, often providing conflicting or incongruous evidence; although it is probable that some association exists, it is likely that EEG patterns and features influence/are mediated by external factors, and further multivariable research is required to determine how 34 . To facilitate application and future evaluation (as in with systematic reviews) it is recommended that prediction models be designed and reported in a systematic manner, such as is outlined by Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis (TRIPOD) guidelines 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in the field of epilepsy research have focused on analyzing the EEG power spectrum (Clemens et al, 2021 ; Irelli et al, 2022 ; Zhong et al, 2022 ). Among these, special attention has been given to the alpha rhythm, which is influenced by cortico-thalamic interactions.…”
Section: Introductionmentioning
confidence: 99%